2020
DOI: 10.3390/biom10071086
|View full text |Cite
|
Sign up to set email alerts
|

Compound Prunetin Induces Cell Death in Gastric Cancer Cell with Potent Anti-Proliferative Properties: In Vitro Assay, Molecular Docking, Dynamics, and ADMET Studies

Abstract: Gastric cancer is the common type of malignancy positioned at second in mortality rate causing burden worldwide with increasing treatment options. Prunetin (PRU) is an O-methylated flavonoid that belongs to the group of isoflavone executing beneficial activities. In the present study, we investigated the anti-proliferative and cell death effect of the compound PRU in AGS gastric cancer cell line. The in vitro cytotoxic potential of PRU was evaluated and significant proliferation was observed. We identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Then, we investigated whether the miR-375/SLC7A11 axis regulates the stemness of GC cells through triggering ferroptosis. Considering that miR-375/SLC7A11 axis may play a role through other forms of cell death instead of inducing ferroptosis, GC cells with miR-375 overexpression or SLC7A11 knockdown were treated with Fer-1 (10 μM), apoptosis inhibitor Z-VAD-FMK (20 μM) [53], or necrosis inhibitor Nec-1 (0.1 mM) [54,55], and following by examining the stemness of GC cells. As shown in Fig.…”
Section: Mir-375 Attenuates the Stemness Of Gc Cells Mainly Through Triggering Ferroptosismentioning
confidence: 99%
“…Then, we investigated whether the miR-375/SLC7A11 axis regulates the stemness of GC cells through triggering ferroptosis. Considering that miR-375/SLC7A11 axis may play a role through other forms of cell death instead of inducing ferroptosis, GC cells with miR-375 overexpression or SLC7A11 knockdown were treated with Fer-1 (10 μM), apoptosis inhibitor Z-VAD-FMK (20 μM) [53], or necrosis inhibitor Nec-1 (0.1 mM) [54,55], and following by examining the stemness of GC cells. As shown in Fig.…”
Section: Mir-375 Attenuates the Stemness Of Gc Cells Mainly Through Triggering Ferroptosismentioning
confidence: 99%
“…Furthermore, RIP3 knockdown, apoptosis inhibitor (Z-VAD-fmk) or necrostatin-1 (Nec-1), the first well-established necroptosis inhibitor that exclusively suppressed RIP1 activity [50], all can in part rescue celastrol-induced GC cell death. Vetrivel et al [51] also came up with similar results through in vitro, vivo experiments, and silico molecular docking and simulation studies. They found that prunetin induced necroptosis-mediated human AGS cell death via activating the RIP3, leading to the phosphorylation of MLKL.…”
Section: Rips and Gastric Cancermentioning
confidence: 67%
“…The activated form of caspase 3 tends to cleave several DNA-dependent protein kinases and poly ADP ribose polymerase (PARP) [ 24 ]. The cleaved form of the protein PARP is recognized as an important apoptotic marker that aids in bringing cellular damage through DNA cleavage and induces apoptotic cell death [ 25 ]. Results obtained from western blot revealed that the apoptotic marker proteins cleaved PARP and cleaved caspase 3 showed significant increased expression in AGS cells upon treatment with PG, as shown in Figure 8 c. These data confirm that PG induces apoptotic cell death in AGS cells.…”
Section: Resultsmentioning
confidence: 99%